15 years of economies in transition: Lessons learned and challenges ahead for the forestry sector. A contribution to the work of the UNECE Timber Committee and the FAO European Forestry Commission - Ilavský, Ján (Finnish Forest Research Institute, 2006)
The paper analyses the outcomes of the transition process in the forest sector which those European countries which previously had centrally planned economies have been undergoing over the last 15 years. It presents an overview of international activities fostering the transition process, carried out within the UNECE/FAO integrated programme of work. The decisive role of MCPFE is recognized: the adoption of Resolution H3 is considered a milestone of international cooperation. The results of its implementation are presented. Cooperation was focused mainly on capacity building, dissemination of knowledge and information, education, training, and transfer of know-how as well as policy and strategy improvement. The main forms of cooperation were study tours, workshops, seminars, exchange of experts and other forms of education. The outcomes and recommendations of several workshops are analyzed in detail.The Joint UNECE/FAO Team of Specialists to monitor and develop assistance in the forest sector and the implementation of the H3 resolution focused its activities on three main areas of assistance: institution building and framework conditions, building of the legal and policy infrastructure; activities related to the development of market oriented and ecologically sound enterprises; and issues of general importance for the protection of forests, forest conservation and sustainable development.The second phase of the cooperation in the transition process has been approved by FAO EFC and UNECE TC during the strategic review of their Integrated programme of work for 2004-2008. A new Strategy for FAO and UNECE forestry and timber activities in the CIS and south east Europe for the period 2005-2010 has been adopted. The tasks of a new UNECE/FAO Team of Specialists on support and contribution to sustainable development of the forest sector in the CIS and South East Europe are presented. Finally, the paper presents the possibilities to transfer lessons learned and experience from the countries which have made more progress in the transition process to less advanced countries as well as the challenges ahead for international cooperation.
Keywords: Itä-Eurooppa; Keski-Eurooppa; metsänkäsittely; metsäpolitiikka; countries in transition; forest management; forest policy